Recurrent Neurogenic Pulmonary Edema Associated With Epileptic Seizures - Takanori Enomoto; Reina Sekiya; Yoshihiko Sasaki; Tsugumi Hosoe; Hazuki Fujimoto; Rei Tsukamoto; Asuka Yoshizaki; Tomomi Terashita; Hiroshi Kamada; Kyosuke Nakata (Respirology Case Reports)
ABSTRACT Neurogenic pulmonary edema (NPE) is acute pulmonary edema triggered by an injury to the central nervous system. NPE associated with epileptic seizures is less common and not well known to recur. We report a case of a 51‐year‐old woman with NPE with recurrent epileptic seizures. The patient was brought to our hospital with two episodes of clonic convulsions. Imaging studies obtained on admission showed bilateral infiltration in the upper lobes of both lungs. The patient was discharged after receiving antiepileptic drugs. NPE may recur with epileptic seizures.